Interplay between Tectonics and Mount Etna’s Volcanism: Insights into the Geometry of the Plumbing System - Patanè, Domenico; Aliotta, Marco; Cannata, Andrea; Cassisi, Carmelo; Coltelli, Mauro; Grazia, Giuseppe Di; Montalto, Placido; Zuccarello, Luciano (IntechOpen, 2011)
None